PENGEMBANGAN MODUL AJAR KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Gea, Elvin Sri Sandy; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani; Telaumbanua, Yakin Niat (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2025)
This study aims to develop a PBL-based teaching module that is valid, practical, and effective in enhancing students’ mathematical problem-solving abilities. The research method employed is development research using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research data include qualitative data in the form of validator comments and quantitative data such as validation scores, student and teacher responses, and the results of problem-solving ability tests. The research instruments consist of learning outcome tests, validation questionnaires, and student and teacher response questionnaires. The findings reveal that the developed teaching module is highly valid with a score of 98.33%. The practicality of the module, as assessed by students and teachers, reached 95.1% and 94.5% respectively. Moreover, the module was proven to be highly effective in improving students’ mathematical problem-solving abilities, achieving an effectiveness score of 95.1%. Therefore, the PBL-based teaching module developed through the ADDIE model meets the criteria of validity, practicality, and effectiveness, and is feasible to be used as a learning resource to enhance students’ mathematical problem-solving skills.